Penyimpangan Perilaku Remaja yang Menimbulkan Fenomena Sosial pada Masyarakat Kelurahan 9 Ilir Lorong Kemas Kota Palembang - Salsabilah Salsabilah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2020)
Deviation of behavior in adolescents with various forms of behavior that exceed the limits has become a social phenomenon at this time and makes society uneasy. There are many causes for juvenile delinquency. This deviant behavior also cannot be tolerated continuously and must be given a solution to deviant behavior through real actions. This article research uses qualitative methods using a case study approach. The data obtained in this study were obtained through two sources, namely through the literature study method where data were obtained from journals, articles, and others. Second, through observation so that the author can directly observe the deviant behavior of adolescents in the sub-district 9 Ilir, the container hall, Palembang, South Sumatra